Robots Worldwide: The Impact of Automation on Employment and Trade - Francesco Carbonero; Ekkehard Ernst; Enzo Weber (ZBW - Leibniz Information Centre for Economics, 2020)
The impact of robots on employment and trade is a highly discussed topic in the academic and public debates. Particularly, there are concerns that automation may threat jobs in emerging countries given the erosion of the labour cost advantage. We provide evidence on the effects of robots on worldwide employment, including emerging economies. To instrument the use of robots, we introduce an index of technical progress, defined as the ability of robots to carry out different tasks. Robots turn out to have a significantly negative impact on worldwide employment. While it is small in developed countries, for emerging economies it amounts to -11 per cent between 2005 and 2014. However, here, there appear positive spillovers especially from robotisation in manufacturing on employment outside manufacturing. Furthermore, we assess cross-country effects, finding that robots in developed countries decrease off-shoring just as employment in emerging economies.
Keywords: J23; O33; F16; 330; robot; technology; employment; off-shoring; re-shoring